2011
DOI: 10.1097/ta.0b013e31823b9ce1
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Intracranial Hemorrhage After Blunt Trauma: Are Patients on Preinjury Anticoagulants and Prescription Antiplatelet Agents at Risk?

Abstract: The incidence of delayed ICH in our study was 1%. However, none of the delayed findings were clinically significant. Among patients on ACAP therapy with a negative CT1 and a normal or unchanged neurologic examination, a routine CT2 is unnecessary. We recommend a period of observation to recognize those patients with symptoms that could be due to delayed ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 13 publications
5
61
1
Order By: Relevance
“…Two studies reported separate results of patients on warfarin and clopidogrel, from which only patients on warfarin were included for this analysis. 12,15 The five studies qualitatively had substantial heterogeneity with noted differences in location, design, and population characteristics ( Table 1). The prospective observational study by Nishijima et al 15 had the largest sample size and showed a prevalence of 6 (95% confidence interval [CI], 2Y15) cases of delayed intracranial hemorrhage per 1,000 patients.…”
Section: Resultsmentioning
confidence: 98%
“…Two studies reported separate results of patients on warfarin and clopidogrel, from which only patients on warfarin were included for this analysis. 12,15 The five studies qualitatively had substantial heterogeneity with noted differences in location, design, and population characteristics ( Table 1). The prospective observational study by Nishijima et al 15 had the largest sample size and showed a prevalence of 6 (95% confidence interval [CI], 2Y15) cases of delayed intracranial hemorrhage per 1,000 patients.…”
Section: Resultsmentioning
confidence: 98%
“…However, the pre-injury use of APAs did not affect morbidity and mortality in retrospective studies in patients with pelvic fractures [412] or general trauma without brain injury [413], but did have an effect in patients with hip fractures [409]. On the contrary, even mild head trauma (GCS 14 to 15) while on APAs is associated with a high incidence of intracranial hemorrhage (ICH) [414-416], and a risk of delayed ICH in this group of patients mandates a longer period of observation [417,418]. Moreover, observational studies found a five-fold increase in traumatic ICH in patients on APAs [419].…”
Section: Resultsmentioning
confidence: 99%
“…The 0.5% rate of delayed development of ICH is similar to previously published reports. 11,20 There are a number of reasons that the use of plasma to reverse warfarin anticoagulation may be ineffective. According to the results of a systematic review of 80 randomized clinical trials, the current guidelines for the administration of FFP are largely empirical.…”
Section: Discussionmentioning
confidence: 99%
“…10 Traumatic brain injury in anticoagulated patients occurs not only acutely but can also develop more slowly and be identified in a delayed fashion. 11,12 Aggressive reversal of anticoagulation has been shown to improve outcome after traumatic intracranial hemorrhage (ICH). 13 Options for reversal of anticoagulation include infusion of fresh frozen plasma (FFP), administration of vitamin K, and use of coagulation factors.…”
Section: Introductionmentioning
confidence: 99%